Falls in Elderly: A Hospital Reality Integrative Review - Reliquias, T.P. (2020)
The objective of this chapter is to identify the risk factors and preponderant causes of falls in the hospital elderly inpatients. A survey on the search engines B-on, EBSCO, and Pubmed, followed by an analysis of the title and abstract is done. Afterwards, the authors analyze all the articles with full text available in Portuguese, Spanish, and English. The most common risk factor for falls in the analyzed articles was being aged above 65 years old. More than half of the articles also mentioned intrinsic factors such as mental disorder, mobility disorder, and use of medication. As for extrinsic factors associated with risk of falls, most of the articles mentioned the characteristics of bed/chair and the obstacles associated with the physical/environmental infrastructures. The prevention strategies for this phenomenon must consider each country and care unit specifically as well as the specific characteristics of its patients, aiming to promote the care quality.